Effects of Enterobacter cloacae extract, selenium nanoparticles and methyl jasmonate on shoot liquid cultures of Sarcocornia fruticosa under salinity stress - Fathia Salem; Raoufa Abdel Rahman; Amel Tammam (BMC Plant Biology)
Abstract Background The in vitro propagation of halophytes is innovative perspective for sustainable agriculture, conservation of natural plants and essential raw materials for industry due to increasing soil salinization and decreasing freshwater availability. Sarcocornia fruticosa, a halophytic plant, may hold promise for biosaline production systems and achieve bioactive products. Understanding the salt tolerance mechanisms of halophytes through elicitors can enhance the production of secondary metabolites, such as phenolics and flavonoids, under saline environment. This study aimed to evaluate the effects of NaCl salinity (700 mM and 1000 mM) on Sarcocornia fruticosa shoot cultures and assess the influence of different elicitors-Enterobacter cloacae extract (BE), selenium nanoparticles (SeNPs) and methyl jasmonate (MeJA) -on the plants growth, physiological and biochemical responses, and isorhamnetin production. Methodology Shoot cultures were grown under controlled conditions with two concentrations of NaCl, alone and in combination with BE (0.5%), SeNPs (100 ppm), or MeJA (50 µM). Growth parameters, photosynthetic pigments, ion accumulation, osmolyte content, oxidative stress marker, enzyme activity, phenolic compound levels, and isorhamnetin production were analyzed to determine the impact of salinity and elicitor treatments on S. fruticosa for 14 days. Results Sarcorcocnia fruticosa exhibited better tolerance up to 700 mM than 1000 mM NaCl, as evidenced by higher dry weights, chlorophyll a/b ratios, and enhanced osmolyte and antioxidant contents. Elicitation both saline cultures with BE and SeNPs improved growth mostly by increasing biomass, pigment contents, K+/Na+ ratios, and reducing lipid peroxidation, however, MeJA reduced the biomass mainly by increasing MDA and Na+ ion accumulation. In contrast, application of all elicitors stimulated the production of phenolic compounds and isorhamnetin, as well as BE can contribute for increasing resistance of S. fruticosa to stressful conditions. Conclusion This study demonstrated that PTC techniques and appropriate elicitors can optimize halophyte propagation and secondary metabolite production under saline conditions. The findings suggest that BE and SeNPs significantly enhanced the growth and biochemical resilience of S. fruticosa under salinity stress, with a notable increase in isorhamnetin production. MEJA.